Deferiprone–resveratrol hybrid attenuates iron accumulation, oxidative stress, and antioxidant defenses in iron-loaded human Huh7 hepatic cells - Li, Jin; Koonyosying, Pimpisid; Korsieporn, Woranontee; Paradee, Narisara; Hutachok, Nuntouchaporn; Xu, Honghong; Ma, Yongmin; Chuljerm, Hataichanok; Srichairatanakool, Somdet (Frontiers in Molecular Biosciences, 2024)
Chronic liver diseases are complications of thalassemia with iron overload. Iron chelators are required to remove excessive iron, and antioxidants are supplemented to diminish harmful reactive oxygen species (ROS), purposing to ameliorate oxidative liver damage and dysfunctions. The deferiprone–resveratrol hybrid (DFP–RVT) is a synthetic iron chelator possessing anti-β-amyloid peptide aggregation, anti-malarial activity, and hepatoprotection in plasmodium-infected mice. The study focuses on investigating the antioxidant, cytotoxicity, iron-chelating, anti-lipid peroxidation, and antioxidant defense properties of DFP–RVT in iron-loaded human hepatocellular carcinoma (Huh7) cells. In the findings, DFP–RVT dose dependently bound Fe(II) and Fe(III) and exerted stronger ABTS•- and DPPH•-scavenging (IC50 = 8.0 and 164 μM, respectively) and anti-RBC hemolytic activities (IC50 = 640 μM) than DFP but weaker than RVT (p < 0.01). DFP–RVT was neither toxic to Huh7 cells nor PBMCs. In addition, DFP–RVT diminished the level of redox-active iron (p < 0.01) and decreased the non-heme iron content (p < 0.01) in iron-loaded Huh7 cells effectively when compared without treatment in the order of DFP–RVT > RVT ∼ DFP treatments (50 µM each). Moreover, the compound decreased levels of hepatic ROS in a dose-dependent manner and the level of malondialdehyde, which was stronger than DFP but weaker than RVT. Furthermore, DFP–RVT restored the decrease in the GSH content and GPX and SOD activities (p < 0.01) in iron-loaded Huh7 cells in the dose-dependent manner, consistently in the order of RVT > DFP–RVT > DFP. Thus, the DFP–RVT hybrid possesses potent iron chelation, antioxidation, anti-lipid peroxidation, and antioxidant defense against oxidative liver damage under iron overload.